Why is a multiplicity of confessions particular to the Reformed tradition? - P. J. Naudé (Acta Theologica)
This article commences with the observation – drawn from a number of standard collections – that a multiplicity of confessions is a particular trait of the Reformed tradition. An explanation for this is then sought with reference to the very conception of theology in the Reformed tradition (Willie Jonker); the spiritual power of the church to declare doctrine (John Calvin), and the relative authority of the confessions themselves (Karl Barth). It is concluded that new confessions will continue to emerge in this tradition as the gospel is proclaimed or put under threat in possible new circumstances in future.